Digital Touch: Towards a Novel User-Experience Design Pedagogy - Mitchell, Val; Wilson, Garrath; Jewitt, Carey; Mackley, Kerstin Leder; Golmohammadi, Lili; Atkinson, Douglas; Price, Sara (Design and Technology Education: An International Journal, 2020)
HCI and Industrial Design are both disciplines that are currently experiencing radical transformation in terms of their identity and scope. HCI has moved beyond its origins in human factors and cognitive psychology towards the proactive and generative design of experience. Industrial Design has similarly evolved from a concern with physical form and function-giving solutions to the holistic design considerations of the user’s experience. Given the complexity and scale of this shifting design landscape, the response of design education must shift in methods and learning and teaching objectives. This paper provides the Design and Technology Education community with a research case study of innovation within HCI education, here situated within the broader context of Industrial Design education. We present a novel pedagogy for designing digital touch communications, developed through an interdisciplinary collaboration of HCI, Industrial Design, and Social Science academics, and advanced through a coursework assignment for 64 undergraduate Industrial Design and Technology students undertaking a User-Experience Design module at the School of Design and Creative Arts, Loughborough University (UK). We discuss the role of low-fidelity experience prototyping of digital touch interactions beyond screens, and the limitations of such an approach when engaged with by novice designers with entrenched material science understanding. We conclude the paper with a call for new educational ‘tools’ to support and scaffold both the learning and teaching of design for digital touch experiences within a User-Experience Design context, and we offer our development of a Designing Digital Touch Toolkit as one such tool.